2018
DOI: 10.1088/1361-6501/aac752
|View full text |Cite
|
Sign up to set email alerts
|

Signal-modelling methods applied to the free-field calibration of hydrophones and projectors in laboratory test tanks

Abstract: PAPER • OPEN ACCESSSignal-modelling methods applied to the free-field calibration of hydrophones and projectors in laboratory test tanks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The tank experiment conducted to demonstrate the feasibility of this approach is described in Sec. 3. In section 4, it is shown, using the experimental data, that the same set of equivalent sources can reproduce the field of a single monopole both in free space and in a tank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tank experiment conducted to demonstrate the feasibility of this approach is described in Sec. 3. In section 4, it is shown, using the experimental data, that the same set of equivalent sources can reproduce the field of a single monopole both in free space and in a tank.…”
Section: Introductionmentioning
confidence: 99%
“…However, both methods are applicable only at sufficiently high frequencies. There exist more sophisticated methods which can be used at acoustic frequencies below the limits imposed by the echo-free time of the test tank [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to calculate the unknown model signal parameters in this method, a linear or a non-linear fitting algorithm is required for a simple (without transients) or an extended (with transients) signal model, respectively. For the latter one, a good starting estimate for model parameters such as resonance frequencies and damping factors is needed for successful application [12].…”
Section: Introductionmentioning
confidence: 99%
“…Blake and Maga [5] were the first to demonstrate through experiments that a nonanechoic water tank satisfies the diffuse-field conditions in the frequency band above the Schroeder cutoff frequency; they also demonstrated that the diffusion field theory commonly used in a reverberation chamber in air is also applicable to a non-anechoic water tank. On the basis of their research work, after decades of development, non-anechoic tanks have been widely used in many fields, including the calibration of underwater transducers, [6][7][8] measurement of the acoustic parameters of underwater acoustic materials, [9,10] and measurement of the sound power radiated from complex structures. [11][12][13][14] The premise of using diffuse-field measurement methods in a non-anechoic water tank is that the modal density in the tank will be sufficiently high that the measurement of the reverberation time will have very good consistency.…”
Section: Introductionmentioning
confidence: 99%